The Influence of Economic Structure to Inequality of Regency/City Revenue in West Kalimantan Province 2010 â€“ 2015 - B1011131099, Syarifah Annisa Fiantiara Alkadri (Jurnal Pembangunan dan Pemerataan, 2017)
The development in a region has the main role in developing the public quality, economic growth, and equity in order to have the better economic condition. Regional development can not carry out as expected, one of the causes is inequality income that occurred in West Kalimantan province. The cause of inequality income occurred because of several factors. Inequality income that occurred within the economy causes the price of staple goods becoming high. The structure of economy of the people of west Kalimantan is still dominated by three main sectors namely agriculture sector, industrial sector, and trade sector. The purpose of this research is to explain the influence of agriculture sector's GDRP, industrial sector's GDRP, and trade sector's GDRP on inequality income of regency/city in West Kalimantan Province on 2010 until 2015. The technique of data analysis being used is multiple regression with random effect model. The sources of data are obtained from Central Bureau of Statistics and Small and Average Micro Enterprise Agency. (X1) has negative influence and is significant on inequality income. (X2) has positive influence and is significant on inequality income. (X3) has negative influence and is not significant on inequality imcome.Â Keywords: inequality income, agriculture sector's GDRP, industrial sector's GDRP, trade sector's GDRP.